Effect of interactive media on the development of children and adolescents: systematic review with meta-analysis - Sabrina da Conceição Guedes; Juliana Nogueira Pontes Nobre; Rosane Luzia de Souza Morais; Rodrigo de Oliveira Mascarenhas; Lívia Rodrigues Santos; Vanessa de Oliveira Martins-Reis; Vinicius Cunha Oliveira; Juliana Nunes Santos (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aim: to investigate through a systematic review of randomized controlled trials (RCTs) the effects of interactive media on the cognitive, language, and motor development of children and adolescents. Methods: Searches were performed with the Medline, AMED, Embase, PEDro, Cochrane, Psychinfo, and ERIC databases in May 2017 with updated in July 2020. For the search strategy, we used descriptors related to "randomized controlled trial", "interactive media" and "children and adolescents up to 18 years old". RCTs that investigated the effectiveness of interactive media in cognitive, motor, and language development of children and adolescents up to 18 years of age with typical development were included. When appropriate, meta-analyses were conducted using a random-effects model. Pooled data were presented using standardized mean difference and 95% confidence interval. We assessed the quality of evidence using the GRADE methodology and the methodological quality using the PEDro scale. Results: of the trials found, 14 references were eligible for this study. The GRADE methodology was used in 13 RCTs. Estimates showed a low level of evidence of a small effect of media use on cognitive development compared to that in the control group and another intervention. No effect on motor and language development. Conclusion: The results of this systematic review do not support claims about the advantages or disadvantages of interactive media in child development. High-quality evidence was found that interactive media is not superior to other interventions for cognitive and language development outcomes and quality of moderate evidence for motor and language development.